Prognostication of Bell’s palsy: a new perspective - Poovathingal, Mary Anne; Gilvaz, Percival; Chacko, Fiju; Baby, Neena (International Journal of Research in Medical Sciences, 2024)
Background: Bell’s palsy is considered as the most frequent cranial neuropathy. Early and adequate risk stratification may help both the patients and the treating physicians in taking informed decisions regarding treatment and understanding their outcomes. We aimed to formulate accessible and sensitive methods of risk stratification in Bell’s palsy by utilizing electrophysiological and hematological parameters. Methods: We prospectively followed up 101 patients with Bell’s palsy over a period of 18 months. Electrophysiological parameters were measured thrice i.e., on the first evaluation and after the first week and first month. The N/L, P/L ratio, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) were documented in steroid naïve cases. Patients were graded in severity based on the Sunnybrook and House Brackmann systems. Results: The mean SB and HB grades at admission were 53.89±24.725 and 3.92±1.04 indicating moderate severity. The mean N/L, P/L ratios and ESR on the first day was 3.46±3.45, 145.42±162.84 and 22.51±21.105 respectively. There was no statistical correlation with severity at any time point. The mean CMAP indices on the 1st day, 1st week and 1st month were 0.585±0.31,0.43±0.26 and 0.45±0.23 respectively. The CMAP index at 1 month was correlating with severity. Blink amplitude ratios were correlating with the HB scores at 1 week and 1 month (p<0.0001 both) and the SB score at 1 month (p<0.0001). Conclusions: Hematological parameters were not correlated to disease severity. However, electrophysiological parameters are correlated to disease severity at one week and one month. Blink amplitude ratio may be a useful indicator for risk stratification of Bell’s palsy patients.